Soft Tissue Thickness Variations of the Nose: A Radiological Study - (:unkn) unknown (OXFORD UNIV PRESS INC, 2020)
Background: Soft tissue thickness (STT) is a major factor affecting the outcome in rhinoplasty. However, limited information is found in the literature on the age- and gender-related variations of the nasal STT. Objectives: The purpose of this study was to measure STT at various landmarks over the nasal framework and compare the age- and gender-related differences. Methods: STT measurements were made at 11 landmarks in 325 patients by employing magnetic resonance imaging. Patients were divided into subgroups to compare the STT differences between female and male and between the age groups as young, middle age, and elderly. Results: Soft tissue was thickest at the nasion and thinnest at the rhinion. The soft tissue coverage was significantly thicker in the male population at the supratip, tip, nasal bones, upper lateral cartilages, and alar lobules, whereas it is thicker in females at the rhinion. Average thickness of the soft tissues over the entire nasal framework increases with age except the rhinion. Conclusions: The STT is variable over different parts of the osteocartilaginous framework. Gender and age influence the STT. The soft tissue is thicker at the distal half of the nose in male patients, and these areas become gradually thicker with age, whereas the soft tissue over the midvault becomes thinner. Increasing age presents a particular challenge to achieve predictable results in rhinoplasty, and an understanding of the soft tissue envelope allows for improved aesthetic outcome.
Keywords: RHINOPLASTY; MANAGEMENT; ANATOMY; VALUES